The expert versus the object : judging fakes and false attributions in the visual arts (Oxford University Press, 2004)
The authenticity of visual art has always commanded the attention of experts, dealers, collectors, and the art-minded public. Is it "real" or "original" is a way of asking what am I buying? What do I own? What am I looking at? And today more sophisticated questions are being asked: How is authenticity determined and what weight does this determination have in court? This book of essays proposes to answer those questions. Three lines of inquiry are basic to determining authenticity: a connoisseur's evaluation, historical documentation or provenance, and scientific testing. A